Sexual objectification decreases women’s experiential consumption (but not material consumption) - Fei Teng; Xue Wang; Ye Yang (Social Influence, 2017)
The current investigation examined our prediction that sexual objectification decreases women’s experiential consumption but not material consumption. Three experiments provided converging support for this prediction. In particular, female participants reported lower tendency to engage in experiential consumption after recalling a past experience of objectification (Studies 1 and 3) and chose a material product over an experiential one after receiving objectifying comments (Study 2). Furthermore, Study 3 found that sexual objectification reduced purchase inclination of experiential products, and this effect did not emerge for material products. These findings contribute to the literature on sexual objectification by showing the impact of sexual objectification on women’s economic decisions and behaviors.